2017
DOI: 10.3892/ijo.2017.4122
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-485 inhibits malignant biological behaviour of glioblastoma cells by directly targeting PAK4

Abstract: Glioblastoma (GBM), which is characterised by rapid growth, cellular heterogeneity, angiogenesis, extensive invasion, hypoxia and necrosis, is the most common histological subtype of glioma in adults. MicroRNA (miRNA) dysregulation is a common feature of human cancers, including GBM. Previous studies have suggested that miRNAs are a novel class of regulatory molecules in various human cancers. Therefore, miRNAs may be investigated as a novel candidate and screening tool in the clinical diagnosis, therapy and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…PAK4 is located at the locus 19q13.2 and it was described as a downstream effector of Ras-related C3 botulinum toxin substrate 1 and cell division control protein 42 homolog (32). PAK4 is upregulated in multiple human cancer types, including colorectal cancer (33), non-small cell lung cancer (34), glioblastoma (35) and gastric cancer (36). PAK4 was implicated in the carcinogenesis and cancer progression by affecting numerous biological processes, including cell proliferation, apoptosis, metastasis and cytoskeletal organisation (37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…PAK4 is located at the locus 19q13.2 and it was described as a downstream effector of Ras-related C3 botulinum toxin substrate 1 and cell division control protein 42 homolog (32). PAK4 is upregulated in multiple human cancer types, including colorectal cancer (33), non-small cell lung cancer (34), glioblastoma (35) and gastric cancer (36). PAK4 was implicated in the carcinogenesis and cancer progression by affecting numerous biological processes, including cell proliferation, apoptosis, metastasis and cytoskeletal organisation (37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that dysregulation of PAK4 expression contributes to the development and progression of various tumors [28,29]. Several studies have reported that PAK4 could be regulated by many miRNAs in various cancers, including miR-485 and miR-199a-3p [30][31][32]. In OSCC, PAK4 serves as a super enhancer-associated candidate oncogene and promotes the proliferation of OSCC cells [33].…”
Section: Discussionmentioning
confidence: 99%
“…PAK4 belongs to a family of serine/threonine kinases that are involved in cell proliferation and migration and in cytoskeletal organization. PAK4 is amplified/over-expressed in non-Hodgkin lymphoma (28), esophageal cancer (29,30), pancreatic cancer (31)(32)(33)(34)(35), breast cancer (36,37), and other cancers (38)(39)(40)(41)(42)(43)(44)(45)(46)(47). Activated PAK4 a) promotes tumorigenesis in breast cancer via activation of the PI3K/AKT signaling pathway (48), b) promotes liver metastasis by phosphorylation of p53 (49), and c) facilitates the epithelial-mesenchymal transition [EMT] in prostate cancer via phosphorylation of the Slug transcription factor (50).…”
Section: Discussionmentioning
confidence: 99%